Tax audit regarding the SIFIDE tax benefit: CAAD arbitral jurisprudence analysis - RIBEIRO, Ana Regina; DINIS, Ana; SERRA, Sara (Revista Jurídica Portucalense, 2025)
The Tax and Customs Authority (AT) is responsible for ensuring settlement and collection, as well as exercising the tax inspection function, with the aim of combating fraud and tax evasion. The “System of Fiscal Incentives for Research and Development” (SIFIDE II) is a measure that allows the deduction of the amount corresponding to research and development (R&D) expenses from the amount of corporate income tax collection (IRC). with increases in investment in R&D, applications for this tax benefit and tax credits requested have increased, as well as conflicts between taxpayers and AT. This study aims to understand the role of the AT as a controlling entity, before the arbitration jurisdiction, analyzing the reasons for litigation and verifying the trend of the arbitration court's decisions in resolving SIFIDE II cases, using as an investigation method, the documental content analysis. The analysis carried out concluded that the tendency is for the superintendent to win in most decisions in SIFIDE II cases, and that, according to the jurisdiction of the Administrative Arbitration Center (CAAD), despite the AT carrying out control and monitoring associated and rigorously, not always the same detection of irregularities, and when detected, they are not always effective irregularities, since our results from the analyzed analyzes end up reversing the corrections made.